Sujeitos da EJA no Brasil contemporâneo: contribuições dos anais da ANPEd (2015-2019) - Almeida, Amanda Carolina Marmo de (Universidade Federal de São Carlos, 2021)
The education of young people and adults needs to consider the diversity of the subjects that compose it, in order to exercise its restorative, equalizing and qualifying functions, as a modality of Basic Education. Therefore, the general objective of this work is to contribute to the construction of pedagogical practices capable of meeting the different profiles of EJA subjects in contemporary Brazil. As specific objectives were delimited: i) Identify which profiles of EJA subjects are in focus in the annals of GT 18 of ANPEd (2015-2019); ii) Understand more deeply who are the subjects of EJA in contemporary Brazil, from the productions present in the referred annals; iii) Knowing which clues are indicated for pedagogical practices in dialogue with these EJA subjects. The work has its theoretical reference in the Freirean perspective, using works by Paulo Freire himself and by contemporary authors inspired by his contributions. This is a bibliographical research, in which the successive stages of reading were used: recognition reading of the bibliographic material, exploratory reading, selective reading, critical reading and interpretive reading, with a view to building an integrative synthesis. The analysis was carried out around two axes: profiles of the subjects in focus and clues for pedagogical practices in dialogue with the subjects. As for the profiles in focus, the productions show: working subjects, women, adolescents and young people, the elderly, people with disabilities and black bodies. It is noticed how some profiles are not present in the productions, such as migrants and refugees, even though this is an audience that is coming to EJA. As for the clues for pedagogical practices in dialogue with the subjects, ten indications were found: education and future objectives, human development, re-signification of the school, permanent education, critical view of society, dialogue between school and non-school knowledge, specificities of EJA, horizontality in the relationship and training of teachers.
Subjects of EJA in contemporary Brazil: contributions from the annals of ANPEd (2015-2019)
Keywords: Educação de Jovens e Adultos; Sujeitos da EJA; Práticas emancipatórias; Adult and young education; Subjects of EJA; Emancipatory practices; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO